2021
DOI: 10.1111/dar.13386
|View full text |Cite
|
Sign up to set email alerts
|

Beyond ‘drinking occasions’: Examining complex changes in drinking practices during COVID‐19

Abstract: Introduction ‘Drinking occasions’ are commonly used to capture quantities of alcohol consumed. Yet this standardised terminology brings with it numerous assumptions and epistemological limitations. We suggest that social changes brought on by COVID‐19 restrictions have influenced routines, patterns of time use and drinking practices, highlighting the need to re‐examine how we conceptualise drinking and ‘drinking occasions’ in alcohol research. Methods This analysis draw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 39 publications
1
18
0
Order By: Relevance
“…Additionally, Caluzzi et al . [36] found that drinking patterns are changing in ways that make it harder to capture them by the concept of a ‘drinking occasion’, as boundaries of occasions are blurred when drinking at home for extended periods. Also, the generalizability of the results to other countries is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Caluzzi et al . [36] found that drinking patterns are changing in ways that make it harder to capture them by the concept of a ‘drinking occasion’, as boundaries of occasions are blurred when drinking at home for extended periods. Also, the generalizability of the results to other countries is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…While the restrictions forced new drinking situations upon the participants and transformed the contours of the home ( Moretti & Maturo, 2021 ), they also made them consider their drinking habits in new ways ( Caluzzi et al, 2021 ; MacLean et al, 2022 ). For some, this meant questioning their abstinence, for others, it meant that they could find new means to define what they like about going out (meeting friends rather than drinking alcohol).…”
Section: Discussionmentioning
confidence: 99%
“…Research in a number of countries has found that COVID-19 lockdowns were associated with increased alcohol purchasing and consumption ( Anderson, Llopis et al, 2020 ; Callinan, Mojica-Perez et al, 2021 ; Daly & Robinson, 2021 ; Koopmann, Georgiadou et al, 2021 ; Lee, Dodge et al, 2021 ; Sugarman & Greenfield, 2021 ) and within Australia, among midlife women in particular ( Neill, Meyer et al, 2020 ; Callinan, Mojica-Perez et al, 2021 ; Callinan, Smit, et al, 2021 ). An Australian study of drinking practices during COVID-19 found changes in how people consumed alcohol and specifically, increases in the frequency of consumption including extensions in the time available to people for consuming alcohol ( Caluzzi, Pennay et al, 2021 ). People who bulk-bought their alcohol compared to those who reported not doing so demonstrated an increased consumption of almost 0.5 drinks per day across the same time-period ( Callinan, Mojica-Perez et al, 2021 ; Callinan, Smit, et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%